Providing significantly enhanced photocatalytic H2 generation using porous PtPdAg alloy nanoparticles on spaced TiO2 nanotubes - Nguyen, Nhat Truong; Ozkan, S.; Hejazi, Seyedsina; Denisov, Nikita; Tomanec, Ondrej; Zboril, R.; Schmuki, Patrik (International Journal of Hydrogen Energy, 2019)
In the present work we introduce a simple approach to produce porous PtPdAg alloy nanoparticles on TiO2 nanotubes by a simple combined sputtering-dewetting-dealloying process. In a first step, three individual metals (Pt, Pd and Ag) were sequentially sputter-deposited on spaced TiO2 nanotubes, followed by a thermal dewetting treatment in Ar to convert these metal layers into ternary PtPdAg alloyed particles. Dealloying was carried out by a selective chemical dissolution of Ag in piranha solution that finally generated porous alloyed nanoparticles located on the TiO2 nanotube walls. The porous PtPdAg-decorated TiO2 nanotubes show enhanced photocatalytic H2 generation in comparison with porous Pt (67% increase) or any monometallic decoration (>120% increase). The photocatalytic enhancement is not only due to the increased number of active sites (larger surface area) of the porous particles but also due to the synergistic effects of the different alloying elements.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Dealloying; Dewetting; Photocatalytic H; PtPd alloy; TiO